Quantifying the role of anticipation in badminton during competition; the impact of situational constraints, game format, match stage and outcome of match - Alder, D.; Broadbent, D. P. (World Badminton Federation, 2017)
The ability to anticipate the actions of opponents in badminton is essential to allow maximal time to select and execute appropriate responses (Alder et al., 2016). A significant bank of work has shown how high level anticipatory skill distinguishes between elite and sub-elite athletes in a range of racket sport contexts. However, research focusing on anticipatory behaviour in badminton is sparse and no research has quantified the role of anticipation during elite level badminton competitions. Therefore, the current project utilised performance analysis techniques to identify: (a) the average response time of elite level badminton players, (b) the frequency of anticipatory behaviours which occur in elite level badminton and (c) how contextual factors such as format of the game impact on both average response time and frequency of anticipatory behaviours.